Analysis of the impact of refactoring on code quality – comparative analysis of two cases - Łukasik, Mariusz; Miłosz, Marek (Journal of Computer Sciences Institute, 2017)
In agile methods, one of the techniques for improving code quality is refactoring. This is a process that employs a number of techniques, modifying the code without changing its functionality, aiming to improve its transparency and reduce vulnerability. You can measure the improvement of the code using different code quality metrics. The paper presents an analysis of the effect of refactoring on static code quality on the example of the open-source project Scuba. The quality of the code was measured at two different points of software development - right before and after refactoring the code. The three most popular sets of object code quality metrics and the Sonarqube tool were used for the measurement. The research clearly demonstrates the significant improvement of static code quality as a result of refactoring.